Facile synthesis of silver-decorated reduced graphene oxide as a hybrid filler material for electrically conductive polymer composites. Issue 20 (6th March 2015) - He, Linxiang; Tjong, Sie Chin
<x xml:space="preserve">Abstract</x> Nano silver-decorated reduced graphene oxide (Ag–RGO) sheets were synthesized by simply dissolving graphite oxide and silver nitrate in N, N-dimethylformamide and keeping the suspension at 90 °C for 12 h.